Socio-spatial visualisations of cultural routes - Catherine Emma (Kate) Jones; Marta Severo; Daniele Guido (Netcom)
Cultural routes, defined as routes of historical importance that geographically represent the shared and living cultural heritage of different countries, have recently gained attention both as tourist destinations and as social repositories of collective local memories. In this paper we argue that the recent development of digital humanities can open interesting new perspectives for the empirical exploration of these routes as cultural objects. Indeed, the availability of new digital traces generated by human activities and social media combined with tools that facilitate the exploration of such traces allow researchers to create new types of fieldwork online. In this paper, we present a case study focused on the Via Francigena cultural route. We added a geographical component to a graph analysis tool called histograph, making it possible to explore and analyse a corpus of more than 8,000 Instagram pictures. We investigate the potential of the prototype to uncover socio-spatial relations related to the itinerary and to hypothesise about the collective memories that the route conveys in this corpus.